Optimization of a PID Controller System for Cobelli Diabetic Model Based Glucose-Insulin Control - Mohammad Faudzi, Ekram; Mahmud, Farhanahani (Evolution in Electrical and Electronic Engineering, 2022)
A clinical study has aided in the development of novel treatments and research for a variety of disorders. Unfortunately, clinical trials are time and expense intensive due to the development of numerous new technologies. Diabetes disease requires long- term testing to have a better knowledge of the disease. For that reason, Cobelli model, a virtual diabetic model is recommended, as it allows for more detailed analysis on the disease. Cobelli model, which is based on a Type I diabetes simulator, is the first computer simulator to be approved by the Food and Drug Administration (FDA). It has paved the door for a new method of comprehending diabetes mellitus. The purpose of this research is to conduct a simulation study using MATLAB Simulink on a PID controller-based insulin-glucose closed loop regulation system based on the Cobelli model for a 24-hour simulation system. In this research, a PID controller-based glucose-insulin closed-loop regulation system based on the Cobelli model Type 1 diabetic was designed using MATLAB Simulink blocks and the PID controller was also optimized using the MATLAB transfer function-based tuning technique. The results of the meal disturbance analysis by reducing carbohydrate (CHO) intake by around 20% and on the analysis of 100%, 70% and 50% of insulin sensitivity have shown a promising outcome in understanding the glucose and insulin dynamics for the insulin-glucose closed loop regulation.